Composition of dirt layers in the bare ice areas near the Yamato Mountains in Queen Maud Land and the Allan Hills in Victoria Land, Antarctica - Katsushima, Takayoshi; Nishio, Fumihiko; Ohmae, Hirokazu; Ishikawa, Masao; Takahashi, Shuhei (1984)
P(論文) Dirt layers of tephra were found on the bare ice surface in the Meteorite Ice Field near the Yamato Mountains, Queen Maud Land, and in the bare ice area near the Allan Hills, Victoria Land. Their age is unknown but supposed to be several to several tens of thousands of years. Their constituent fragments are well-sorted and composed mainly of volcanic glass shards with minor amounts of crystal fragments. Glass shards of tephra from the Yamato Mountains region have a composition of tholeiitic andesite which is low alkali and high iron but not so enriched in titanium, and the associated crystal fragments consist of calcic plagioclase, subcalcic clinopyroxene, orthopyroxene and magnetite. Such character of island arc tholeiite of the tephra indicates its source to be some volcano in the South Sandwich Islands. On the other hand, the tephra from the Allan Hills region is composed of glass shards with trachybasaltic composition and crystal fragments of titanaugite, calcic plagioclase, kaersutite, olivine, rhonite and titanomagnetite. Some young volcano of the McMurdo Volcanic Group is suggested to be a possible source of the tephra. departmental bulletin paper